Cytotoxic Activity of Antineoplastic Agents on Fertility: A Systematic Review - Gabriel Acácio de Moura; Paula Bruno Monteiro (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2020)
Abstract Objective: To analyze the long-term effects of antineoplastic treatments on patient fertility. Selection of Studies: The studies were selected through the New PubMed, Scielo and Lilacs databases along with references used for the creation of the present work. For the selection of studies, articles published between the periods from January 1, 2015 to April 6, 2020 in the English, Portuguese and Spanish languages were used. As inclusion criteria: cohort studies and studies conducted in vitro. As exclusion criteria: review articles, reported cases, studies that do not address thematic reproduction, studies that do not address the cancer theme, articles that used animals, articles that address the preservation of fertility and articles in duplicate in the bases. Data Collection: The collected data included: age of the patient at the beginning of treatment, type of neoplasm, type of antineoplastic treatment, chemotherapy used, radiotherapy dosage, radiotherapy site, effect of antineoplastic agents on fertility and number of patients in the study. Data Synthesis: Thirty studies were evaluated, antineoplastic chemotherapy agents and radiotherapy modulate serum hormone levels, reduces germ cell quantities and correlated with an increase in sterility rates. The effects mentioned occur in patients in the prepubertal and postpubertal age. Conclusion: Antineoplastic treatments have cytotoxic effects on the germ cells leading to hormonal modulation, and pubertal status does not interfere with the cytotoxic action of therapies.